Alternative wax recovery from Apis mellifera: Different combs size effect (Research, Society and Development, 2021)
The bee wax has great historical importance and has been present since the evolution of civilizations. Currently, besides several uses of the wax, its recovery is indispensable for the rational management of swarms by beekeepers. The wax can be recovered from the combs using different techniques, however the conditions of the pre-extraction combs, such as their size, can influence the wax yield. Thus, studies must still be carried out to standardize the techniques and processes for extracting the wax from the combs, in order to improve the wax yield. This study aimed to evaluate the recovery of Apis mellifera wax according to the size of the comb using an alternative extraction technique. First, the influence of the comb size on wax recovery was evaluated. We used brown color combs, which were broken down into four sizes, each size representing a treatment, namely: Treatment I - 25 cm2; Treatment II - 16 cm2; Treatment III - 9 cm2 and Treatment IV - 4 cm2. Combs were submitted to the "internal strain" technique for 30 minutes of extraction, after boiling the water. The wax recovery was superior in treatment III (P